Profil Keterampilan Bermain Tenis Meja Mahasiswa - Azmi, Syamil Aliyul; Juliantine, Tite; Gumilar, Agus (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2024)
ABSTRACT This research aims to see an overview of the table tennis playing skills of PJKR FPOK UPI students. The method in this research is ex post facto, with all 24 students taking table tennis courses as respondents. Respondents have conducted 12 lecture meetings with table tennis learning material and a playing skills learning activity that lasts two hours in each session. The results of this research show that 46% of students' backhand strokes in the profile of students' table tennis playing skills are in the very good category, and 4% are still in the poor category, while for forehand strokes in students' table tennis playing skills 21% are in the very good category. However, there are still 13% of respondents in the poor category; of course, this is a serious concern to be able to overcome this problem. The conclusion is that the backhand stroke in the profile of students' table tennis playing skills for backhand and forehand strokes falls into the very good category. Keywords: Skills, Playing Table Tennis, Students